Kinship Politics: Political Elite’s Desire for Power Versus the Ethics of Consequentialism - Nurul Annisa Hamudy (Ministry of Home Affairs, 2021)
Kinship Politics as a form of control of political space by the elites makes it easier for their family members to win an election against other candidates. Kinship Politics is prone to abuse of power that benefits just a few people. The author studied this problem using philosophical reflection. Humans have a relentless desire to achieve success or felicity (as Hobbes stated) that requires humans to continue accumulating power. Power must be attained and defended, although it means forgoing the ethical foundation. For this reason, this study aimed to analyse the moral consequences of the desire for power of the political elites in the 2020 Regional-Head Election (Pilkada) through an ethical lens. This study used descriptive and literature study method, as well as a qualitative approach, and the results of the study showed that the kinship politics in the 2020 Pilkada should not be continued in the perspective of consequentialism ethic that emphasizes the goal of happiness for as many people as possible, since Kinship politics that concentrated the power in one person supported by the circle of power will benefit only a handful of people.